Enforcing Exact Boundary and Initial Conditions in the Deep Mixed Residual Method (CSIAM Transactions on Applied Mathematics, 2021)
Boundary and initial conditions are important for the well-posedness of partial differential equations (PDEs). Numerically, these conditions can be enforced exactly in classical numerical methods, such as finite difference method and finite element method. Recent years, we have witnessed growing interests in solving PDEsby deep neural networks (DNNs), especially in the high-dimensional case. However,in the generic situation, a careful literature review shows that boundary conditionscannot be enforced exactly for DNNs, which inevitably leads to a modeling error. Inthis work, based on the recently developed deep mixed residual method (MIM), wedemonstrate how to make DNNs satisfy boundary and initial conditions automatically by using distance functions and explicit constructions. As a consequence, theloss function in MIM is free of the penalty term and does not have any modeling error.Using numerous examples, including Dirichlet, Neumann, mixed, Robin, and periodicboundary conditions for elliptic equations, and initial conditions for parabolic and hyperbolic equations, we show that enforcing exact boundary and initial conditions notonly provides a better approximate solution but also facilitates the training process.